Analyzing the Tax Benefits from Employee Stock Options - BABENKO, ILONA; TSERLUKEVICH, YURI (Journal of Finance, 2009)
ABSTRACT Employees tend to exercise stock options when corporate taxable income is high, shifting corporate tax deductions to years with higher tax rates. If firms paid employees the same dollar value in wages instead of stock options, the average annual tax bill for large U.S. companies would increase by $12.6 million, or 9.8%. These direct tax benefits of options increase in the convexity of the tax function. In addition, profitable firms can realize indirect tax benefits because stock options increase debt capacity. Although tax minimization is probably not the main motive for option grants, firms with larger potential tax benefits grant more options.